2021
DOI: 10.1016/j.dnarep.2020.103030
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and mutational studies of a novel 3-methlyadenine DNA glycosylase II from the hyperthermophilic Thermococcus gammatolerans

Abstract: The hyperthermophilic and radioresistant euryarchaeon Thermococcus gammatolerans encodes a putative 3-methlyadenine DNA glycosylase II (Tg-AlkA).Herein, we report biochemical characterization and catalytic mechanism of Tg-AlkA.The recombinant Tg-AlkA can excise hypoxanthine (Hx) and 1-methlyadenine (1-meA) from dsDNA with varied efficiencies at high temperature. Notably, Tg-AlkA is a bi-functional glycosylase, which is sharply distinct from all the reported AlkAs.Biochemical data show that the optimal temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…A number of structural and biochemical studies have revealed damaged base recognition and removal mechanisms of Escherichia coli AlkA ( Nakabeppu et al, 1984 ; Bjelland and Seeberg, 1996 ; Labahn et al, 1996 ; Yamagata et al, 1996 ; O’Brien and Ellenberger, 2004 ), thus enabling the enzyme to be a model alkylated DNA glycosylase. Currently, only two archaeal AlkA homologs have been reported from the hyperthermophilic euryarchaeon Archaeoglobus fulgidus and Thermococcus gammatolerans ( Figure 1 ; Birkeland et al, 2002 ; Mansfield et al, 2003 ; Leiros et al, 2007 ; Jiang et al, 2021 ). Thus, our understanding on biochemical function and catalytic mechanism of archaeal AlkA remains incomplete.…”
Section: Excision Of Hx From Dna By Archaeal Alkamentioning
confidence: 99%
See 4 more Smart Citations
“…A number of structural and biochemical studies have revealed damaged base recognition and removal mechanisms of Escherichia coli AlkA ( Nakabeppu et al, 1984 ; Bjelland and Seeberg, 1996 ; Labahn et al, 1996 ; Yamagata et al, 1996 ; O’Brien and Ellenberger, 2004 ), thus enabling the enzyme to be a model alkylated DNA glycosylase. Currently, only two archaeal AlkA homologs have been reported from the hyperthermophilic euryarchaeon Archaeoglobus fulgidus and Thermococcus gammatolerans ( Figure 1 ; Birkeland et al, 2002 ; Mansfield et al, 2003 ; Leiros et al, 2007 ; Jiang et al, 2021 ). Thus, our understanding on biochemical function and catalytic mechanism of archaeal AlkA remains incomplete.…”
Section: Excision Of Hx From Dna By Archaeal Alkamentioning
confidence: 99%
“…Biochemical data have demonstrated that A. fulgidus AlkA and T. gammatolerans AlkA are able to remove Hx from dsDNA ( Mansfield et al, 2003 ; Jiang et al, 2021 ). Although, the two protein hosts are hyperthermophiles, T. gammatolerans AlkA displays biochemical characteristics distinct from A. fulgidus AlkA.…”
Section: Excision Of Hx From Dna By Archaeal Alkamentioning
confidence: 99%
See 3 more Smart Citations